Modulating Single‐Atom Palladium Sites with Copper for Enhanced Ambient Ammonia Electrosynthesis. Issue 1 (27th October 2020) - Han, Lili; Ren, Zhouhong; Ou, Pengfei; Cheng, Hao; Rui, Ning; Lin, Lili; Liu, Xijun; Zhuo, Longchao; Song, Jun; Sun, Jiaqiang; Luo, Jun; Xin, Huolin L.
Abstract: The electrochemical reduction of N2 to NH3 is emerging as a promising alternative for sustainable and distributed production of NH3 . However, the development has been impeded by difficulties in N2 adsorption, protonation of *NN, and inhibition of competing hydrogen evolution. To address the issues, we design a catalyst with diatomic Pd‐Cu sites on N‐doped carbon by modulation of single‐atom Pd sites with Cu. The introduction of Cu not only shifts the partial density of states of Pd toward the Fermi level but also promotes the d‐2π* coupling between Pd and adsorbed N2, leading to enhanced chemisorption and activated protonation of N2, and suppressed hydrogen evolution. As a result, the catalyst achieves a high Faradaic efficiency of 24.8±0.8 % and a desirable NH3 yield rate of 69.2±2.5 μg h −1  mgcat. −1, far outperforming the individual single‐atom Pd catalyst. This work paves a pathway of engineering single‐atom‐based electrocatalysts for enhanced ammonia electrosynthesis. Abstract : We have designed an efficient N2 reduction reaction (NRR) catalyst with diatomic Pd‐Cu sites on N‐doped porous carbon by modifying single‐atom Pd sites with Cu. The catalyst achieves high Faradaic efficiency and a desirable yield rate for NH3 electrosynthesis under ambient conditions, outperforming the individual single‐atom counterparts.